Microsatellite marker analysis of Haemonchus contortus populations from Pakistan suggests that frequent benzimidazole drug treatment does not result in a reduction of overall genetic diversity. Issue 1 (December 2016) - Chaudhry, Umer; Redman, E.; Ashraf, Kamran; Shabbir, Muhammad; Rashid, Muhammad; Ashraf, Shoaib; Gilleard, John
Abstract Background The impact of drug selection pressure on the overall genetic diversity of parasitic nematode populations in the field is poorly understood. In this study, we address this issue for the small ruminant parasiteHaemonchus contortus in the Punjab, Pakistan. This region provides an opportunity to compareH. contortus populations that have been subjected to a prolonged period of frequent benzimidazole drug treatments on government farms with parasite populations that have been exposed to little or no drug treatment in neighbouring pastoral herds. Methods AdultH. contortus worms were collected from the abomasa of small ruminants from three government farms frequently using benzimidazole drugs, and closed to animal movement, for over 30 years and also from from eighteen pastoral herds subject to minimal drug selection. The frequency of three known benzimidazole resistance associated mutations was determined in each parasite population. For the seven parasite populations in which resistance mutations were found, the diversity, geographical distribution and phylogenetic relationships of isotype-1 β-tubulin benzimidazole resistance haplotypes were determined. In addition, the genetic diversity of the parasite populations on the three government farms were compared with those from four pastoral herds. Results The F200Y (TA C) resistance mutation was present at a very high frequency inH. contortus populations from government herds, but not from pastoral herds, consistent with their respective drug selection histories. Population genetic analysis, using a panel of microsatellite markers, revealed that there was little genetic differentiation among the parasite populations with no significant difference in the overall genetic diversity between government and pastoral herds. In addition, sequence analysis of the isotype-1 β-tubulin locus revealed multiple F200Y (TA C) haplotypes demonstrating soft selective sweeps even in government herds with little or no contemporary parasite migration. Conclusions The results suggest that, although the frequent drug treatment used on government farms has selected for a high frequency of benzimidazole resistance mutations, there has been little or no reduction in the overall genetic diversity of the selected parasite populations.